Clustering education policy in secondary provision: Impact on higher education and job market - Alam, Gazi Mahabubul (SAGE Publications, 2021)
International commitment is to address all forms of imbalanced and discriminatory situations experienced within the education system. While students of secondary provision in many developed countries enjoy the liberty of choosing their desired subjects from different areas (i.e., science, business, and arts), students in some de-veloping counterparts are restricted to consider one cluster. With a policy support, students of the science cluster can procure higher education (HE) in any area, while students from other clusters are restricted to study HE in their respective area only. By virtue of this policy, the limited scope of HE and jobs in the areas of business and arts is being occupied by science graduates because of one- way traffic that favors sci-ence cluster. This has a grave impact on the HE and job market, which is the central focus of this research. We failed to find such studies conducted in the context of a developing nation. Considering this, the article is the first of its kind. Given the differ-entiated nature of research questions, multiple techniques were used to collect the data. However, this research bears the norms of qualitative method. Findings confirm that having been denied access to HE, secondary graduates especially from the busi-ness cluster, dropped out without furthering their education. This has deteriorated the quality of HE and job performance—more precisely, it has deprived students of the business and arts clusters. This research suggests a revision of the prevailing pol-icy to address these constraints.